End-of-Life Management Options for Agricultural Mulch Films in the United States—A Review - Madrid, Brenda; Wortman, Sam; Hayes, Douglas G.; DeBruyn, Jennifer M.; Miles, Carol; Flury, Markus; Marsh, Thomas L.; Galinato, Suzette P.; Englund, Karl; Agehara, Shinsuke; DeVetter, Lisa Wasko (Frontiers in Sustainable Food Systems, 2022)
Polyethylene plastic mulches are widely used in specialty cropping systems in the United States due to the horticultural benefits they provide. However, polyethylene mulch is reapplied seasonally, generating large volumes of plastic waste that contribute to plastic pollution concerns. This review synthesizes scientific and industry findings to provide a state of current end-of-life options of polyethylene mulch in the United States and identifies opportunities that can improve plastic waste management with a special emphasis on soil-biodegradable plastic mulches. Major points discussed are: (1) polyethylene mulch use in specialty cropping systems, (2) economic, environmental and waste management impacts of polyethylene mulch use, (3) current common end-of-life pathways of used polyethylene mulch, (4) use of soil-biodegradable plastic mulch as an alternative to reduce the amount of plastic waste in the environment and offset the negative impacts associated with residual non-degradable plastics, (5) socioeconomic factors that reduce the adoption of soil-biodegradable plastic mulch, and (6) limitations of soil-biodegradable mulch. The results of this review conclude that recycling and upcycling of used polyethylene mulch can be a more sustainable disposal option, however cleaning and decontaminating used polyethylene mulch is costly and commercial technology is often not accessible nor economically viable in many regions in the current economic and political situation. To make recycling a viable pathway in the future, research and policy developments are necessary to refine and encourage recycling. Soil-biodegradable plastic mulches can offer an additional opportunity to help address these limitations, but they are not permitted in organic agriculture in the United States. Further studies are necessary to address the current knowledge gaps and gain a better understanding of the factors influencing the degradation of soil-biodegradable mulches under diverse field conditions. Improved end-of-life strategies should continue to be pursued that balance sustainable use of plastic mulch while minimizing environmental risks.